2021
DOI: 10.3389/fmed.2021.799078
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Year Outcomes of Implantation of Posterior Chamber Phakic Intraocular Lens With a Central Port for Moderate to High Ametropia

Abstract: Purpose: To assess the 8-year clinical outcomes of implantation of an implantable collamer lens (ICL) with a central port (KS-Aquaport; EVO-ICL) for moderate to high myopia and myopic astigmatism.Methods: This retrospective study comprised a total of 177 eyes of 106 patients with spherical equivalents of −7.99 ± 3.33 D [mean ± standard deviation], who underwent EVO-ICL implantation. We evaluated the safety, efficacy, predictability, stability, and adverse events of the surgery, at 1 month, and 1, 2, 4, 6, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Cataract is one of the common complications after ICL implantation [161], and early cataract after ICL implantation is mostly related to surgical trauma, while late cataract is mostly related to contact between ICL and the lens itself [162]. The incidence increases with the passage of postoperative time [68,74,77,84,142,[163][164][165][166][167][168][169]. It has been reported that the incidence of cataract within 10 years after ICL implantation is 12.1% [78] and the risk of cataract formation will increase seven years after ICL implantation [114].…”
Section: Cataractmentioning
confidence: 99%
“…Cataract is one of the common complications after ICL implantation [161], and early cataract after ICL implantation is mostly related to surgical trauma, while late cataract is mostly related to contact between ICL and the lens itself [162]. The incidence increases with the passage of postoperative time [68,74,77,84,142,[163][164][165][166][167][168][169]. It has been reported that the incidence of cataract within 10 years after ICL implantation is 12.1% [78] and the risk of cataract formation will increase seven years after ICL implantation [114].…”
Section: Cataractmentioning
confidence: 99%
“…We described the details of the surgical procedures in our previous reports [4,[13][14][15][16]. In brief, on the day of surgery, dilating and topical anesthetic agents were applied.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The EVO Visian implantable collamer lens (EVO Visian ICL TM , STAAR Surgical, Monrovia, CA, USA), a posterior chamber phakic intraocular lens with central port technology, has been established as a long-term safe and effective means to correct moderate to high ametropia [1][2][3][4] and has also been shown to be more effective in reducing significant postoperative complications such as cataract formation than the conventional ICL without a central port [1][2][3][4][5], possibly resulting from the improved circulation of the aqueous humor to the anterior surface of the crystalline lens [6,7]. The ICL is generally fixated to the horizontal plane through a temporal corneal incision according to the manufacturer's recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Longer follow-up studies on ICL V4c report likewise reassuring results. 39,40 The older ICL models had a risk for pupillary block glaucoma mainly because of inadequate preoperative iridotomies and/or excessive ICL vaulting. 10 The V4c model eliminates the need of a YAG-iridotomy or iridectomy and is believed to reduce the risk for pupil block and thus angle closure by allowing sufficient aqueous flow through the central port.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in endothelial cell density after ICL V4c implantation was 2.4% at 5 years, 2.6% at 7 years, and 3.6 ± 7.0% at 8 years postoperatively, without significant endothelial cell density loss (>20%) in all 3 articles. [37][38][39] On the other hand, publications on postoperative complications and adverse effects after LASIK surgery consisted of epithelial ingrowth (0.1% and 2.7%), dry eye disease (1.1%), post-LASIK keratectasia (0%), infectious keratitis (0.1%), diffuse lamellar keratitis (DLK) (2.1%), and corneal opacification (among which DLK) (0.9%). 5,32 Of interest, 1 follow-up study of 12 years (n = 68) reported a zero incidence of postoperative complications (epithelial ingrowth, DLK, severe dry eye, and keratectasia).…”
Section: Discussionmentioning
confidence: 99%